2020
DOI: 10.17159/2519-0105/2020/v75no4a3
|View full text |Cite
|
Sign up to set email alerts
|

Sterilisation and single-use of endodontic files - a short report

Abstract: INTRODUCTION: In many countries, endodontic files continue to be sterilised and reused in multiple clinical cases as the alternative of single-use of these instruments is avoided due to financial reasons. METHODS: A survey was performed including South African general dental practitioners and specialist prosthodontists to determine the current endodontic file sterilisation methods in place and the adoption rate of single-use protocols of both hand and engine-driven instruments. RESULTS: The majority of respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Comparing with the situation in another country, with different socioeconomic conditions from the previous study, the survey evaluated the reuse of endodontic instruments in South Africa. The results showed that 81.5% of participants reused automated NiTi endodontic instruments 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing with the situation in another country, with different socioeconomic conditions from the previous study, the survey evaluated the reuse of endodontic instruments in South Africa. The results showed that 81.5% of participants reused automated NiTi endodontic instruments 7 .…”
Section: Discussionmentioning
confidence: 99%
“…However, even with the manufacturers' indications, epidemiological studies show that operators routinely reuse NiTi instruments. Such methods are mainly due to the social, economic, and financial conditions in which these professionals are inserted 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The assumption that gemination has a single root canal and fusion has multiple root canals is controversial. The fusion of a normal tooth with supernumeraries still results in a normal tooth count 5 . Given the features suggestive of both diagnoses, this case indeed presented a diagnostic dilemma.…”
Section: Case Imagementioning
confidence: 99%
“…1,2 Occasionally, there is some confusion regarding the correct use of these terms, and an exact diagnosis is not always possible clinically. [3][4][5][6] Concrescence as dental twin anomaly consists only of a union between two or more teeth over the cementum in either deciduous or permanent dentition. 1,6,7 This means that only the roots of two adjacent teeth are fused.…”
Section: Introductionmentioning
confidence: 99%
“…15 In single cases, cone-beam computed tomography (CBCT) is used for the diagnosis of double teeth and treatment planning. [4][5][6]9,15,16 For example, Buchanan et al concluded in a case of a 12-year-old girl with a double gemination that the use of three-dimensional (3D) imaging greatly aids treatment planning and communication with the patient in such uncommon and unusual cases. 4 Double teeth are not an exact dental diagnosis, but are often used as a catch-all term when the diagnosis is unclear.…”
Section: Introductionmentioning
confidence: 99%